Comparison of properties of small-scale ion flux fluctuations in the flank magnetosheath and in the solar wind. Issue 2 (15th July 2016) - Riazantseva, M.O.; Budaev, V.P.; Rakhmanova, L.S.; Zastenker, G.N.; Šafránková, J.; Němeček, Z.; Přech, L.
Abstract: We present a comparison of spectral and statistical properties of ion flux fluctuations in the turbulent solar wind and in the flank Earth's magnetosheath. We use the data of the BMSW device operating in frame of the SPECTR-R mission with an extremely high-time resolution (up to ∼30 ms). Fourier spectra of ion flux fluctuations are systematically analyzed both in the solar wind and in the magnetosheath on the inertial scale and on a transition to the dissipation scale in the range of 0.01–10 Hz. We show that ion flux fluctuation spectra in the flank magnetosheath are similar to those observed in the solar wind and we demonstrate the presence of the break at frequencies of ∼1–2 Hz. Spectra are slightly steeper in the flank magnetosheath but the break frequency is near twice less in a comparison to the solar wind. The magnetosheath ion flux turbulent flow is intermittent as it was shown earlier for the solar wind. We discuss the level of intermittency of ion flux fluctuations in both regions and we determine the characteristics of structure functions. Finally, we demonstrate extended self-similarity in the magnetosheath.